Studi Implementasi Kebijakan Kota Layak Anak (KLA) di Kota Pekanbaru - Mustiqowati Ummul Fithriyyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
The policy imlementation of children appropriate city known as (KLA) is intended as a real effort to unite children rights issues into the planning and construction of district / city. Children care development is basically a condition for the respect, protection and fulfillment of children's rights.The policy imlementation of children appropriate city known as (KLA) in Pekanbaru has been launched through the establishment of the Task Force, but yet there appears to be a significant change. In general it can be said that the issue of Children has not been a priority in policy and budgeting in Pekanbaru city government and child protection movement has not been done optimally. The changes are not expected to be significant. This research is to know